Lone fatherhood: experience and perception, choice and constraint - Fox, Elizabeth. (2002)
This thesis explores men's experience of raising children alone, and addresses a central question for men's engagement in care: Can men mother? If men can mother, what makes this possible? To what extent are breadwinning identities and mothers' care for children barriers to men's engagement in caring? If mothering is a constitutive activity based on a response to the perceived needs of children, what does caring mean to fathers, and what is the impact of caring for children in the absence of maternal mediation?